2013
DOI: 10.1371/journal.pone.0063224
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Dehydroepiandrosterone-Sulfate and Other Parameters of Adrenal Function in Acute Ischemic Stroke

Abstract: Background and PurposeAcute stroke has a high morbidity and mortality. We evaluated the predictive value of adrenal function testing in acute ischemic stroke. MethodsIn a cohort of 231 acute ischemic stroke patients, we measured dehydroepiandrosterone (DHEA), DHEA-Sulfate (DHEAS), cortisol at baseline and 30 minutes after stimulation with 1 ug ACTH. Delta cortisol, the amount of rise in the 1 ug ACTH-test, was calculated. Primary endpoint was poor functional outcome defined as modified Rankin scale 3–6 after 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 71 publications
3
10
0
1
Order By: Relevance
“…Eleven were excluded based on study design. Overall, 25 cohort studies, with a total of 92 489 CVD patients, were included in our systematic review . For each of these studies, we extracted items including year of publication, name of the first author, country of origin of the research group, sample number of studies included, design used in the studies, quality evaluation of the studies, follow‐up time, confounder for adjustments, DHEAS concentration gradient, and end point.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven were excluded based on study design. Overall, 25 cohort studies, with a total of 92 489 CVD patients, were included in our systematic review . For each of these studies, we extracted items including year of publication, name of the first author, country of origin of the research group, sample number of studies included, design used in the studies, quality evaluation of the studies, follow‐up time, confounder for adjustments, DHEAS concentration gradient, and end point.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies investigated deficient DHEAS level and fatal cardiovascular events, 7 studies investigated low DHEAS and nonfatal cardiovascular events, and 1 study reported DHEAS with fatal/nonfatal cardiovascular events separately. In the meta‐analysis, the pooled estimates for the lowest compared with the highest category of baseline DHEAS indicated a significant increased risk for fatal cardiovascular events without heterogeneity ( I 2 =0%): pooled risk ratio, 1.58 (95% CI, 1.30–1.91; P <0.00001 [Figure ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological role of DHEA is poorly understood, but there are clear indications that it modulates the immune response and influences both pro-and anti-inflammatory cytokine release (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that this increase was not only observed in the blood, but also in urine and saliva [5,25]. The etiology of increase cortisol level in ischemic stroke is not obvious and some studies claim that ischemic stroke acts like a stressor and activates pituitary -adrenal axis [5,26]. This finding is also seen in intracerebral hemorrhage [14,27].…”
Section: Discussionmentioning
confidence: 95%